Enhanced Glucose Uptake in Human Liver Cells and Inhibition of Carbohydrate Hydrolyzing Enzymes by Nordic Berry Extracts - Giang Thanh Thi Ho; Thi Kim Yen Nguyen; Eili Tranheim Kase; Margey Tadesse; Hilde Barsett; Helle Wangensteen (Molecules, 2017)
A Western lifestyle with low physical activity and a diet rich in sugar, fat and processed food contribute to higher incidences of diabetes and obesity. Enhanced glucose uptake in human liver cells was observed after treatment with phenolic extracts from different Nordic berries. All berry extracts showed higher inhibition against α-amylase and α-glucosidase than the anti-diabetic agent acarbose. Total phenolic content and phenolic profiles in addition to antioxidant activities, were also investigated. The berries were extracted with 80% methanol on an accelerated solvent extraction system (ASE) and then purified by C-18 solid phase extraction (SPE). Among the ASE methanol extracts, black chokeberry, crowberry and elderberry extracts showed high stimulation of glucose uptake in HepG2 cells and also considerable inhibitory effect towards carbohydrate hydrolyzing enzymes. SPE extracts with higher concentrations of phenolics, resulted in increased glucose uptake and enhanced inhibition of α-amylase and α-glucosidase compared to the ASE extracts. Crowberry and cloudberry were the most potent 15-lipoxygenase inhibitors, while bog whortleberry and lingonberry were the most active xanthine oxidase inhibitors. These results increase the value of these berries as a component of a healthy Nordic diet and have a potential benefit against diabetes.